index d3ccc98..d0897ef 100644 (file)
@@ -28,14 +28,14 @@ internal nodes?]
We'll be using trees where the nodes are integers, e.g.,

-       let t1 = Node ((Node ((Leaf 2), (Leaf 3))),
-                      (Node ((Leaf 5),(Node ((Leaf 7),
-                                             (Leaf 11))))))
+       let t1 = Node (Node (Leaf 2, Leaf 3),
+                      Node (Leaf 5, Node (Leaf 7,
+                                             Leaf 11)))
.
___|___
|     |
.     .
-       _|__  _|__
+       _|_   _|__
|  |  |  |
2  3  5  .
_|__
@@ -46,9 +46,9 @@ Our first task will be to replace each leaf with its double:

let rec treemap (newleaf : 'a -> 'b) (t : 'a tree) : 'b tree =
match t with
-           | Leaf x -> Leaf (newleaf x)
-           | Node (l, r) -> Node ((treemap newleaf l),
-                                 (treemap newleaf r));;
+           | Leaf i -> Leaf (newleaf i)
+           | Node (l, r) -> Node (treemap newleaf l,
+                                  treemap newleaf r);;

`treemap` takes a function that transforms old leaves into new leaves,
and maps that function over all the leaves in the tree, leaving the
@@ -76,7 +76,7 @@ decide to do something else to the leaves without needing to rewrite
`treemap`.  For instance, we can easily square each leaf instead by
supplying the appropriate `int -> int` operation in place of `double`:

-       let square x = x * x;;
+       let square i = i * i;;
treemap square t1;;
- : int tree =ppp
Node (Node (Leaf 4, Leaf 9), Node (Leaf 25, Node (Leaf 49, Leaf 121)))
@@ -87,53 +87,53 @@ to each subpart of the computation.  In other words, `treemap` has the

In general, we're on a journey of making our treemap function more and
-more flexible.  So the next step---combining the tree transducer with
+more flexible.  So the next step---combining the tree transformer with
-tree that is ready to accept any `int->int` function and produce the
+tree that is ready to accept any `int -> int` function and produce the
updated tree.

-\tree (. (. (f2) (f3))(. (f5) (.(f7)(f11))))
+\tree (. (. (f 2) (f 3)) (. (f 5) (. (f 7) (f 11))))

-       \f    .
-         ____|____
-         |       |
-         .       .
-       __|__   __|__
-       |   |   |   |
-       f2  f3  f5  .
-                 __|___
-                 |    |
-                 f7  f11
+       \f      .
+          _____|____
+          |        |
+          .        .
+        __|___   __|___
+        |    |   |    |
+       f 2  f 3  f 5  .
+                    __|___
+                    |    |
+                   f 7  f 11

That is, we want to transform the ordinary tree `t1` (of type `int
-tree`) into a reader object of type `(int->int)-> int tree`: something
-that, when you apply it to an `int->int` function returns an `int
-tree` in which each leaf `x` has been replaced with `(f x)`.
+tree`) into a reader object of type `(int -> int) -> int tree`: something
+that, when you apply it to an `int -> int` function `f` returns an `int
+tree` in which each leaf `i` has been replaced with `f i`.

With previous readers, we always knew which kind of environment to
expect: either an assignment function (the original calculator
simulation), a world (the intensionality monad), an integer (the
enough for now to expect that our reader will expect a function of
-type `int->int`.
+type `int -> int`.

-       type 'a reader = (int->int) -> 'a;;  (* mnemonic: e for environment *)
-       let reader_unit (x : 'a) : 'a reader = fun _ -> x;;
-       let reader_bind (u: 'a reader) (f : 'a -> 'c reader) : 'c reader = fun e -> f (u e) e;;
+       type 'a reader = (int -> int) -> 'a;;  (* mnemonic: e for environment *)
+       let reader_unit (a : 'a) : 'a reader = fun _ -> a;;
+       let reader_bind (u: 'a reader) (f : 'a -> 'b reader) : 'b reader = fun e -> f (u e) e;;

It's easy to figure out how to turn an `int` into an `int reader`:

-       let int2int_reader (x : 'a): 'b reader = fun (op : 'a -> 'b) -> op x;;
+       let int2int_reader : 'a -> 'b reader = fun (a : 'a) -> fun (op : 'a -> 'b) -> op a;;
int2int_reader 2 (fun i -> i + i);;
- : int = 4

But what do we do when the integers are scattered over the leaves of a
tree?  A binary tree is not the kind of thing that we can apply a
-function of type `int->int` to.
+function of type `int -> int` to.

let rec treemonadizer (f : 'a -> 'b reader) (t : 'a tree) : 'b tree reader =
match t with
-           | Leaf x -> reader_bind (f x) (fun x' -> reader_unit (Leaf x'))
+           | Leaf i -> reader_bind (f i) (fun i' -> reader_unit (Leaf i'))
| Node (l, r) -> reader_bind (treemonadizer f l) (fun x ->
@@ -143,7 +143,7 @@ something of type `'a` into an `'b reader`, and I'll show you how to
turn an `'a tree` into an `'a tree reader`.  In more fanciful terms,
the `treemonadizer` function builds plumbing that connects all of the
leaves of a tree into one connected monadic network; it threads the

- : int tree =
@@ -151,7 +151,7 @@ monad through the leaves.

Here, our environment is the doubling function (`fun i -> i + i`).  If
-int2int_reader t1`) to a different `int->int` function---say, the
+int2int_reader t1`) to a different `int -> int` function---say, the
squaring function, `fun i -> i * i`---we get an entirely different
result:

@@ -159,24 +159,24 @@ result:
- : int tree =
Node (Node (Leaf 4, Leaf 9), Node (Leaf 25, Node (Leaf 49, Leaf 121)))

-Now that we have a tree transducer that accepts a monad as a
+Now that we have a tree transformer that accepts a reader monad as a
parameter, we can see what it would take to swap in a different monad.
For instance, we can use a state monad to count the number of nodes in
the tree.

type 'a state = int -> 'a * int;;
-       let state_unit x i = (x, i+.5);;
-       let state_bind u f i = let (a, i') = u i in f a (i'+.5);;
+       let state_unit a = fun s -> (a, s);;
+       let state_bind_and_count u f = fun s -> let (a, s') = u s in f a (s' + 1);;

Gratifyingly, we can use the `treemonadizer` function without any
modification whatsoever, except for replacing the (parametric) type
+`'b reader` with `'b state`, and substituting in the appropriate unit and bind:

let rec treemonadizer (f : 'a -> 'b state) (t : 'a tree) : 'b tree state =
match t with
-           | Leaf x -> state_bind (f x) (fun x' -> state_unit (Leaf x'))
-           | Node (l, r) -> state_bind (treemonadizer f l) (fun x ->
-                              state_bind (treemonadizer f r) (fun y ->
+           | Leaf i -> state_bind_and_count (f i) (fun i' -> state_unit (Leaf i'))
+           | Node (l, r) -> state_bind_and_count (treemonadizer f l) (fun x ->
+                              state_bind_and_count (treemonadizer f r) (fun y ->
state_unit (Node (x, y))));;

Then we can count the number of nodes in the tree:
@@ -199,10 +199,19 @@ Then we can count the number of nodes in the tree:
Notice that we've counted each internal node twice---it's a good
exercise to adjust the code to count each node once.

+<!--
+A tree with n leaves has 2n - 1 nodes.
+This function will currently return n*1 + (n-1)*2 = 3n - 2.
+To convert b = 3n - 2 into 2n - 1, we can use: let n = (b + 2)/3 in 2*n -1
+
+But I assume Chris means here, adjust the code so that no corrections of this sort have to be applied.
+-->
+
+
One more revealing example before getting down to business: replacing
`state` everywhere in `treemonadizer` with `list` gives us

-       # treemonadizer (fun x -> [ [x; square x] ]) t1;;
+       # treemonadizer (fun i -> [ [i; square i] ]) t1;;
- : int list tree list =
[Node
(Node (Leaf [2; 4], Leaf [3; 9]),
@@ -212,16 +221,21 @@ Unlike the previous cases, instead of turning a tree into a function
from some input to a result, this transformer replaces each `int` with
a list of `int`'s.

+<!--
+We don't make it clear why the fun has to be int -> int list list, instead of int -> int list
+-->
+
+
Now for the main point.  What if we wanted to convert a tree to a list
of leaves?

type ('a, 'r) continuation = ('a -> 'r) -> 'r;;
-       let continuation_unit x c = c x;;
-       let continuation_bind u f c = u (fun a -> f a c);;
+       let continuation_unit a = fun k -> k a;;
+       let continuation_bind u f = fun k -> u (fun a -> f a k);;

let rec treemonadizer (f : 'a -> ('b, 'r) continuation) (t : 'a tree) : ('b tree, 'r) continuation =
match t with
-           | Leaf x -> continuation_bind (f x) (fun x' -> continuation_unit (Leaf x'))
+           | Leaf i -> continuation_bind (f i) (fun i' -> continuation_unit (Leaf i'))
| Node (l, r) -> continuation_bind (treemonadizer f l) (fun x ->
continuation_bind (treemonadizer f r) (fun y ->
continuation_unit (Node (x, y))));;
@@ -230,7 +244,7 @@ We use the continuation monad described above, and insert the
`continuation` type in the appropriate place in the `treemonadizer` code.
We then compute:

-       # treemonadizer (fun a c -> a :: (c a)) t1 (fun t -> []);;
+       # treemonadizer (fun a k -> a :: (k a)) t1 (fun t -> []);;
- : int list = [2; 3; 5; 7; 11]

We have found a way of collapsing a tree into a list of its leaves.
@@ -241,7 +255,7 @@ note that an interestingly uninteresting thing happens if we use the
continuation unit as our first argument to `treemonadizer`, and then
apply the result to the identity function:

-       # treemonadizer continuation_unit t1 (fun x -> x);;
+       # treemonadizer continuation_unit t1 (fun i -> i);;
- : int tree =
Node (Node (Leaf 2, Leaf 3), Node (Leaf 5, Node (Leaf 7, Leaf 11)))

@@ -249,25 +263,25 @@ That is, nothing happens.  But we can begin to substitute more
interesting functions for the first argument of `treemonadizer`:

(* Simulating the tree reader: distributing a operation over the leaves *)
-       # treemonadizer (fun a c -> c (square a)) t1 (fun x -> x);;
+       # treemonadizer (fun a k -> k (square a)) t1 (fun i -> i);;
- : int tree =
Node (Node (Leaf 4, Leaf 9), Node (Leaf 25, Node (Leaf 49, Leaf 121)))

(* Simulating the int list tree list *)
-       # treemonadizer (fun a c -> c [a; square a]) t1 (fun x -> x);;
+       # treemonadizer (fun a k -> k [a; square a]) t1 (fun i -> i);;
- : int list tree =
Node
(Node (Leaf [2; 4], Leaf [3; 9]),
Node (Leaf [5; 25], Node (Leaf [7; 49], Leaf [11; 121])))

(* Counting leaves *)
-       # treemonadizer (fun a c -> 1 + c a) t1 (fun x -> 0);;
+       # treemonadizer (fun a k -> 1 + k a) t1 (fun i -> 0);;
- : int = 5

We could simulate the tree state example too, but it would require
generalizing the type of the continuation monad to

-       type ('a -> 'b -> 'c) continuation = ('a -> 'b) -> 'c;;
+       type ('a, 'b, 'c) continuation = ('a -> 'b) -> 'c;;

---------------------
@@ -276,37 +290,37 @@ Of course, by now you may have realized that we have discovered a new

type 'a tree = Leaf of 'a | Node of ('a tree) * ('a tree);;
-       let tree_unit (x: 'a) = Leaf x;;
+       let tree_unit (a: 'a) = Leaf a;;
let rec tree_bind (u : 'a tree) (f : 'a -> 'b tree) : 'b tree =
match u with
-           | Leaf x -> f x
+           | Leaf a -> f a
| Node (l, r) -> Node ((tree_bind l f), (tree_bind r f));;

For once, let's check the Monad laws.  The left identity law is easy:

-    Left identity: bind (unit a) f = bind (Leaf a) f = fa
+    Left identity: bind (unit a) f = bind (Leaf a) f = f a

To check the other two laws, we need to make the following
observation: it is easy to prove based on `tree_bind` by a simple
induction on the structure of the first argument that the tree
resulting from `bind u f` is a tree with the same strucure as `u`,
-except that each leaf `a` has been replaced with `fa`:
+except that each leaf `a` has been replaced with `f a`:

-\tree (. (fa1) (. (. (. (fa2)(fa3)) (fa4)) (fa5)))
+\tree (. (f a1) (. (. (. (f a2) (f a3)) (f a4)) (f a5)))

.                         .
__|__                     __|__
|   |                     |   |
-                     a1  .                    fa1  .
+                     a1  .                   a1  .
_|__                     __|__
|  |                     |   |
-                        .  a5                    .  fa5
+                        .  a5                    .  f a5
bind         _|__       f   =        __|__
|  |                    |   |
-                       .  a4                   .  fa4
+                       .  a4                   .  f a4
__|__                   __|___
|   |                   |    |
-                     a2  a3                 fa2  fa3
+                     a2  a3                f a2  f a3

Given this equivalence, the right identity law

@@ -323,26 +337,26 @@ As for the associative law,
we'll give an example that will show how an inductive proof would
proceed.  Let `f a = Node (Leaf a, Leaf a)`.  Then

-\tree (. (. (. (. (a1)(a2)))))
-\tree (. (. (. (. (a1) (a1)) (. (a1) (a1)))  ))
+\tree (. (. (. (. (a1) (a2)))))
+\tree (. (. (. (. (a1) (a1)) (. (a1) (a1)))))

.
____|____
.               .            |       |
bind    __|__   f  =    __|_    =      .       .
|   |           |   |        __|__   __|__
-               a1  a2         fa1 fa2       |   |   |   |
+               a1  a2        f a1 f a2      |   |   |   |
a1  a1  a1  a1

Now when we bind this tree to `g`, we get

-                  .
-              ____|____
-              |       |
-              .       .
-            __|__   __|__
-            |   |   |   |
-           ga1 ga1 ga1 ga1
+                   .
+              _____|______
+              |          |
+              .          .
+            __|__      __|__
+            |   |      |   |
+          g a1 g a1  g a1 g a1

At this point, it should be easy to convince yourself that
using the recipe on the right hand side of the associative law will